Poszukiwanie znaczeń sztuki naskalnej na podstawie badań poświęconych współczesnej twórczości dzieci - Pankiewicz, Marek (Folia Praehistorica Posnaniensia, 2016)
Child art has long been a subject of research. Books and papers on the issue inspired me to look at rock art through the prism of studies on the artistic works of the little ones. This paper discusses a pilot study that I have conducted and offers some theoretical considerations on reading art.